If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7p-8=3(3p-5)
We move all terms to the left:
7p-8-(3(3p-5))=0
We calculate terms in parentheses: -(3(3p-5)), so:We get rid of parentheses
3(3p-5)
We multiply parentheses
9p-15
Back to the equation:
-(9p-15)
7p-9p+15-8=0
We add all the numbers together, and all the variables
-2p+7=0
We move all terms containing p to the left, all other terms to the right
-2p=-7
p=-7/-2
p=3+1/2
| 4^x/2=8 | | 0.02+0.5a=-0.3 | | 12p=3=11 | | -2(z+4)-(3z-2)=-2-(6z-2) | | -7x—5=9 | | t-23+6t=3(3t-9) | | 6(3x–9)=–18 | | m=-2;(-1,4) | | x^2+2x^2=210^2 | | –4+2x=10x | | -144=3(1-7b) | | 0.25+18=1x | | 360=6x+12 | | .25+18=1x | | -7(-4v+4)=-107 | | 7(-4+4x)+5=-107 | | 5n+23=-9-3n | | -85=-6(1-3m)-7 | | (4+i)(4-1)=0 | | 2x+6.5=15 | | 180=9x+38 | | t+33+5t=3(4t-5) | | 8(8+3x)=-104 | | 10/20=15/x | | 21-3q=18 | | 4(4+4n)=96 | | y/9=8/7 | | -203=7(6n+7) | | 180+70x=945-60x | | 85=-5(1+3p) | | 5p*(-5=150 | | b+1=9-b |